Trajectories of self-rated health before and after retirement: Evidence from two cohort studies - Stenholm S.; Virtanen M.; Pentti J.; Oksanen T.; Kivimäki M.; Vahtera J. (BMJ Publishing Group, 2022)
Objectives: Previous studies have produced conflicting findings on the health consequences of retirement. We aimed at identifying trajectories of self-rated health over retirement transition using repeated measurements and examined which preretirement factors predicted membership to each trajectory.
Methods: The study population consisted of Finnish public sector employees from two independent cohorts (Finnish Public Sector Study (FPS), n=5776 with a 4-year follow-up interval; and Finnish Retirement and Aging Study (FIREA), n=2796 with a 1-year follow-up interval). Both cohorts included assessment of self-rated health one to three times before and one to three times after retirement (average number of measurement points: 3.7 in FPS and 3.5 in FIREA). We used latent trajectory analysis to identify trajectories of self-rated health.
Results: In both cohorts four similar trajectories were identified: ‘Sustained good health’ (47% in FPS and 74% in FIREA), ‘From good to suboptimal health’ (19% and 6%), ‘From suboptimal to good health’ (14% and 8%) and ‘Sustained suboptimal health’ (20% and 12%). There were more women and persons in high occupational status in the ‘From suboptimal to good health’ trajectory group when compared with ‘Sustained suboptimal health’ trajectory group in FPS. Those in the trajectory ‘From good to suboptimal health’ had lower occupational status and higher job strain in comparison with those in the ‘Sustained good health’ trajectory in both cohorts.
Conclusions: A large majority of public sector employees maintain their perceived health status during retirement transition. Adverse trajectory in self-rated health relate to low occupational status and work-related stressors.